1998
DOI: 10.1007/s004360050402
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat distribution and coexistence of Microcotylidae (Monogenea) on the gills of the striped mullet Mugil cephalus  : chance or competition?

Abstract: The two monogenean species Metamicrocotyla cephalus and Microcotyle mugilis have specific microhabitats on the gills of Mugil cephalus on which they may or may not coexist. M. cephalus is found in sector 1 of the posterior hemibranch of arch I. M. mugilis is found on the filaments of sector 5 of the posterior hemibranch of arch I. The coexistence of these two monogenean species on the same fish does not induce a change in their respective distribution, except for a marked preference of M. cephalus for the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
1
28
1
1
Order By: Relevance
“…These include Dactylogyrus spp. parasitizing Rutilus rutilus (see Koskivaara, 1992), microcotylids infecting Mugil cephalus (see Ei Hafidi et al, 1998) and Polylabris mamaevi and Tetrancistrum nebulosi on Siganus fuscescens (see Yang et al, 2006), but such a relationship was often statistically insignificant. However, in the present study, there was a significant positive interspecific correlation between P. coioidesis and P. serrani on Epinephelus spp.…”
Section: Discussionmentioning
confidence: 99%
“…These include Dactylogyrus spp. parasitizing Rutilus rutilus (see Koskivaara, 1992), microcotylids infecting Mugil cephalus (see Ei Hafidi et al, 1998) and Polylabris mamaevi and Tetrancistrum nebulosi on Siganus fuscescens (see Yang et al, 2006), but such a relationship was often statistically insignificant. However, in the present study, there was a significant positive interspecific correlation between P. coioidesis and P. serrani on Epinephelus spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, preference for fish side has been recorded with some monogenes. Preference for the right side was observed on Dactylogyrus amphibothrium [32] and Microcotyle mugilis while preference for the left side was observed concerning Metamicrocotyle cephalus [14] and Dactylogyrus valeti [21].…”
Section: Discussionmentioning
confidence: 99%
“…Data available are less abundant and are those of [6][7][8]. The majority of works on the distribution of gill parasites are related to Monogenea [6,7,[12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. tilapiae preferred gill arch II and the distal zone. Various works also showed that microhabitat selection is common among fish gill monogeneans and that the choice of attachment site varies with the species (El Hafidi et al, 1998;Tombi et al, 2010;Le Roux et al, 2011;Sujana, 2015). The majority of the representatives of the studied component community are preferentially found on gill arches I and II and on the anterior hemibranch.…”
Section: Discussionmentioning
confidence: 99%